Dosimetric properties of an amorphous silicon EPID for verification of modulated electron radiotherapy. Issue 6 (22nd May 2013) - Chatelain, Cécile; Vetterli, Daniel; Henzen, Dominik; Favre, Pascal; Morf, Daniel; Scheib, Stefan; Fix, Michael K.; Manser, Peter
Abstract : Purpose: To investigate the dosimetric properties of an electronic portal imaging device (EPID) for electron beam detection and to evaluate its potential for quality assurance (QA) of modulated electron radiotherapy (MERT). Methods: A commercially available EPID was used to detect electron beams shaped by a photon multileaf collimator (MLC) at a source‐surface distance of 70 cm. The fundamental dosimetric properties such as reproducibility, dose linearity, field size response, energy response, and saturation were investigated for electron beams. A new method to acquire the flood‐field for the EPID calibration was tested. For validation purpose, profiles of open fields and various MLC fields (square and irregular) were measured with a diode in water and compared to the EPID measurements. Finally, in order to use the EPID for QA of MERT delivery, a method was developed to reconstruct EPID two‐dimensional (2D) dose distributions in a water‐equivalent depth of 1.5 cm. Comparisons were performed with film measurement for static and dynamic monoenergy fields as well as for multienergy fields composed by several segments of different electron energies. Results: The advantageous EPID dosimetric properties already known for photons as reproducibility, linearity with dose, and dose rate were found to be identical for electron detection. The flood‐field calibration method was proven to be effective and the EPID was capable to accurately reproduce the dose measured in water at 1.0 cm depth for 6 MeV, 1.3 cm for 9 MeV, and 1.5 cm for 12, 15, and 18 MeV. The deviations between the output factors measured with EPID and in water at these depths were within ±1.2% for all the energies with a mean deviation of 0.1%. The average gamma pass rate (criteria: 1.5%, 1.5 mm) for profile comparison between EPID and measurements in water was better than 99% for all the energies considered in this study. When comparing the reconstructed EPID 2D dose distributions at 1.5 cm depth to film measurements, the gamma pass rate (criteria: 2%, 2 mm) was better than 97% for all the tested cases. Conclusions: This study demonstrates the high potential of the EPID for electron dosimetry, and in particular, confirms the possibility to use it as an efficient verification tool for MERT delivery.